The profession of pharmacy technician in the light of the Act on Certain Medical Professions - Anna Pilarska-Romanowska; Agnieszka Ewa Zimmermann (Polish Pharmaceutical Society, 2024)
The primary aim of health professional regulations is to improve the quality of health services, as well as to increase the level of patient safety. So far, the professions regulated by professional laws were the professions of doctor, dentist, nurse, midwife, physiotherapist, pharmacist, paramedic, laboratory diagnostician and feldsher. The Act on Certain Medical Professions introduces huge changes in the performance of fifteen medical professions that have not been regulated in Polish law so far. Another novelty is the inclusion of so many professions in one legal act. The primary goal of the new act is to increase the level of patient safety by preventing patients from the provision of healthcare and other services by people who do not have appropriate qualifications. Therefore, its content includes specific guidelines regarding the necessary education, improving one's qualifications and the need for continuous professional development. A crucial part of each act regulating medical professions is the one concerning the scope of liability in the event of improper performance of the profession. This allows to bear responsibility for violations of regulations by practitioners of medical professions, regardless of civil or criminal liability. The provisions of the Act also covered pharmacy technicians. According to the Act on Certain Medical Professions, apart from appropriate education, a pharmacy technician will also have to fulfil a number of other requirements. A new duty for pharmacy technicians will be the need to enter the Central Register of Persons Authorized to Practice a Medical Profession. The aim of this article is to present the most important changes taking place in the profession of a pharmacy technician due to the entry into force of the Act on Certain Medical Professions. It is worth remembering that statutory regulation of a profession does not only mean that the legislator imposes new obligations on people practicing it. It also provides legal protection for the professional title of a pharmacy technician.